2004
DOI: 10.1158/0008-5472.can-04-1177
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin E2 Enhances Pancreatic Cancer Invasiveness through an Ets-1-Dependent Induction of Matrix Metalloproteinase-2

Abstract: Accumulating evidence suggests an important role for cyclooxygenase-2 (COX-2) in the pathogenesis of a wide range of malignancies. Here we tested the hypothesis that the COX-2 product prostaglandin E 2 (PGE 2 ) increases cellular invasive potential by inducing matrix metalloproteinase-2 (MMP-2) expression and activity through an extracellular signalregulated kinase (ERK)/Ets-1-dependent mechanism in pancreatic cancer. PANC-1 and MIAPaCa-2 pancreatic cancer cells were treated with PGE 2 or rofecoxib, a selectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
73
0
3

Year Published

2005
2005
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(84 citation statements)
references
References 46 publications
7
73
0
3
Order By: Relevance
“…Both cyclooxygenases (PTGS1 and PTGS2) are identified as overexpressed in PDAC by our meta-analysis (Figure 3). These findings underline the importance of the cyclooxygenase system for the PDAC development since it has been demonstrated that inhibition of PTGS2 leads to reduced invasiveness of pancreatic cancer cells (Ito et al, 2004). Taken together, we were able to identify an overexpression of genes associated with CAM-DR and with increased invasiveness and metastasis in primary pancreatic adenocarcinoma.…”
Section: Discussionsupporting
confidence: 73%
“…Both cyclooxygenases (PTGS1 and PTGS2) are identified as overexpressed in PDAC by our meta-analysis (Figure 3). These findings underline the importance of the cyclooxygenase system for the PDAC development since it has been demonstrated that inhibition of PTGS2 leads to reduced invasiveness of pancreatic cancer cells (Ito et al, 2004). Taken together, we were able to identify an overexpression of genes associated with CAM-DR and with increased invasiveness and metastasis in primary pancreatic adenocarcinoma.…”
Section: Discussionsupporting
confidence: 73%
“…Until recently, the mode of action of NSAID was thought to be solely through inhibition of Cox, which, along with its products such as prostaglandin E 2 , is up-regulated in tumors and enhances the invasion of cancer cells via matrix metalloproteinase-2 (MMP-2; ref. 13). However, the chemopreventive effects of these compounds may also occur, in part, through gene modulation.…”
Section: Introductionmentioning
confidence: 99%
“…Ets-1 is one of transcription factors activated by ERK1/2 signaling pathway. 27) The correlation between MMP-7 and Ets-1 expression has been observed in HCC tissues, and the forced expression of Ets-1 significiantly induced MMP-7 expression in HepG2 cells. 18) We are currently investigating whether Ets-1 is associated with isofraxidin-mediated inhibition of MMP-7 expression.…”
Section: Discussionmentioning
confidence: 95%